2016
DOI: 10.1186/s12870-016-0811-7
|View full text |Cite
|
Sign up to set email alerts
|

Rol genes enhance the biosynthesis of antioxidants in Artemisia carvifolia Buch

Abstract: BackgroundThe secondary metabolites of the Artemisia genus are well known for their important therapeutic properties. This genus is one of the valuable sources of flavonoids and other polyphenols, but due to the low contents of these important metabolites, there is a need to either enhance their concentration in the original plant or seek alternative sources for them. The aim of the current study was to detect and enhance the yield of antioxidant compounds of Artemisia carvifolia Buch. HPLC analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 51 publications
3
10
0
1
Order By: Relevance
“…These results could be attributed to the functional role of the rolB gene in inducing secondary metabolite biosynthesis in hairy roots by activating their biosynthetic genes. These results are in accordance with those revealed by Chung et al [ 11 ] and Dilshad et al [ 27 ] who found that the expression levels of flavonoid biosynthetic genes in the hairy roots of Brassica rapa and Artemisia carvifolia , respectively, were higher than those in the normal roots.…”
Section: Resultssupporting
confidence: 93%
“…These results could be attributed to the functional role of the rolB gene in inducing secondary metabolite biosynthesis in hairy roots by activating their biosynthetic genes. These results are in accordance with those revealed by Chung et al [ 11 ] and Dilshad et al [ 27 ] who found that the expression levels of flavonoid biosynthetic genes in the hairy roots of Brassica rapa and Artemisia carvifolia , respectively, were higher than those in the normal roots.…”
Section: Resultssupporting
confidence: 93%
“…W. coagulans, F. cretica, and H. nepalensis are known to have different flavonoid and phenolic compounds with several biological activities in central nerves system. Although the role of flavonoids and phenolics in these plants has not been defined as antidepressant, however these compounds are well known for antidepressant effect [ 7 , 55 , 56 ]. So, it can be suggested that these compounds may be responsible for antidepressant effect.…”
Section: Resultsmentioning
confidence: 99%
“…Right paw of each rat was injected with 0.1 ml (1%) carrageenan for edema induction. The paw volume was measured before and after the carrageenan induction at 0 h, 1 h, 2 h, 3 h, and 4 h by using Plethysmometer (UGO 7140, Basile) [ 7 ]. The percent inhibition of edema was calculated by using the following relation: where N.C represents negative control group and S.G represents sample group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Крім того, використання культур «бородатих» коренів, отриманих шляхом трансформації з використанням ґрунтових фітопатогенних бактерій Аgrobacterium rhizogenes, дозволяє провести не тільки порівняння виживаності таких культур та коренів контрольних нетрансформованих рослин, але й встановити вплив генетичної трансформації на вторинний метаболізм в умовах абіотичного стресу, спричиненого наявністю токсичного металу у середовищі. Такі дослідження можуть базуватися на тому факті, що перенесення rol генів А. rhizogenes, які є індукторами змін вторинного метаболізму [8][9][10][11], можуть призводити до активізації синтезу у клітинах трансформованих коренів сполук з антиоксидантними або відновлювальними властивостями.…”
unclassified